Isolation and characterization of Ralstonia solanacearum causing wilt disease in tomato. (14th December 2022) - Mekonnen, Habtamu; Kibret, Mulugeta; Assefa, Fassil
Abstract: Bacterial wilt, caused by Ralstonia solanacearum, is the most serious and common disease that affects tomatoes globally. Tomato bacterial wilt is among the worst and most prevalent diseases in Ethiopia. It causes substantial tomato production losses in various parts of the country. The purpose of this study was to isolate and characterize Ralstonia solanacearum causing wilt disease in tomato. Ralstonia solanacearum isolates were isolated from wilted tomato stem samples using Casamino Acid Peptone Glucose Agar (CPG) plates and incubated at 28 ± 2 °C for 48 h. Bacterial colonies showing big, irregular smooth, and cream-white, were considered presumptive Ralstonia solanacearum isolates. Morphological, biochemical, and pathological characterization were used for identification of the bacterium. Biovar identification was determined based on the utilization of carbohydrates. A total of 76 Ralstonia solanacearum isolates were screened and identified as Ralstonia solanacearum . Out of all the isolates, 28.9% of the isolates were isolated from Mecha, followed by Fogera (27.6%), Dera (23.7%), and Bahir Dar Zuria (19.7%) districts. The pathogenicity test results also revealed that all Ralstonia solanacearum isolates tested caused wilt symptoms in tomato plants and had varying levels of virulence on tomato plants, ranging from highly virulent (G1B1, G2M2, G3H1, and G4F3 isolates) to moderately virulent (G1B1, G2M1, G2M3, G3H2, G4F1, and G4F2 isolates). Besides, 48 Ralstonia solanacearum isolates were identified as Biovar II, and 28 Ralstonia solanacearum isolates were identified as biovar III. The overall findings of this study could provide valuable information for integrated tomato bacterial wilt disease management. The molecular characterization should be carried out on Ralstonia solanacearum in different host ranges.